Survey of Mississippi Mosquito Blood Meals for Vertebrate Host Identification - Ber, Jessica Lynn; Goddard, Jerome; Outlaw, Diana (Journal of the American Mosquito Control Association, 2021)
Exploring particular mosquito and vertebrate relationships provide insight to potential transmission of several agents of disease. In the current study, the relationship between white-tailed deer ( Odocoileus virginianus ) and mosquitoes was explored by identifying blood meals within mosquitoes captured throughout Mississippi between June and September of 2013 and 2017. We captured 72 bloodfed mosquitoes between 2 collection years, with a majority of specimens identified as Culex erraticus or Psorophora mathesoni . Seventy-nine percent (26/33) of blood meals in Cx. erraticus originated from the white-tailed deer. These findings implicate mosquitoes may primarily be feeding on white-tailed deer in rural areas of Mississippi.